Effective authentication of Placenta Hominis - Yat-Tung Lo; Mavis Hong-Yu Yik; Pang-Chui Shaw (BMC, 2018)
Abstract Background Human placenta is used to make the medicinal product Placenta Hominis in Asian countries. With its therapeutic benefits and limited supply, intentional or inadvertent adulteration is found in the market. In order to enforce the implementation of product description laws and protect customer rights, we established a hierarchical protocol involving morphological, chemical, biochemical and molecular diagnosis to authenticate this medicinal product. Methods Ten samples claimed as Placenta Hominis were collected from herbal shops in China, Hong Kong and Taiwan. Species-specific diagnostic primers for human, cow, deer and sheep were designed for PCR amplification and subsequent DNA sequencing for species identification. Commercially available pregnancy test strip was used to detect human chorionic gonadotropin (hCG), and progesterone competitive ELISA kit was used to detect the presence of progesterone in samples. The presence of starch in samples was tested by adding small amount of iodine solution onto the samples. Results Among the ten samples studied, results showed that no cow, deer and sheep DNA sequence was found in all samples. Five samples were genuine with the presence of human DNA, hCG and progesterone accompanied with the absence of starch fillers. On the other hand, four samples were adulterants which may be made from starch products. In addition, a sample was found as a mixture of Placenta Hominis and starch fillers, and it did not conform to the product requirement of Placenta Hominis. Conclusions The comprehensive protocol developed involving morphological, chemical, biochemical and molecular diagnosis provides an accurate method to regulatory bodies and testing laboratories for the quality control of Placenta Hominis.